1999
DOI: 10.1172/jci6443
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed cyclin D3 contributes to retaining the growth inhibitor p27 in the cytoplasm of thyroid tumor cells

Abstract: The majority of thyroid carcinomas maintain the expression of the cell growth suppressor p27, an inhibitor of cyclin-dependent kinase-2 (Cdk2). However, we find that 80% of p27-expressing tumors show an uncommon cytoplasmic localization of p27 protein, associated with high Cdk2 activity. To reproduce such a situation, a mutant p27 devoid of its COOH-terminal nuclear-localization signal was generated (p27-NLS). p27-NLS accumulates in the cytoplasm and fails to induce growth arrest in 2 different cell lines, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 31 publications
4
110
0
1
Order By: Relevance
“…Since p27 kip1 phosphorylation leads to its turnover, one possibility is that, by directly or indirectly increasing the rate of p27 kip1 phosphorylation, the PI3K/Akt pathway targets it to degradation and that PTEN would decrease the rate of p27 kip1 turnover by preventing activation of this pathway. Accordingly, we have recently shown that p27 kip1 expression is lost in approximately 40% of primary thyroid carcinomas (Baldassarre et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since p27 kip1 phosphorylation leads to its turnover, one possibility is that, by directly or indirectly increasing the rate of p27 kip1 phosphorylation, the PI3K/Akt pathway targets it to degradation and that PTEN would decrease the rate of p27 kip1 turnover by preventing activation of this pathway. Accordingly, we have recently shown that p27 kip1 expression is lost in approximately 40% of primary thyroid carcinomas (Baldassarre et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…The human thyroid carcinoma cell lines used in this study have been previously described (Baldassarre et al, 1999). All cell lines were grown in Dulbecco's modiĀ®ed eagle medium (DMEM) containing 10% fetal calf serum.…”
Section: Cell Lines and Tissue Samplesmentioning
confidence: 99%
“…Alternatively, this could be due to an unknown mechanism for the elimination of p27. In some tumors, p27 is aberrantly localized to the cytoplasm [49,[63][64][65][66]. Sequestration of p27 in the cytoplasm may serve to block p27's inhibitory activity toward cyclin E/cdk2 complexes and allow increased proliferation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…It is interesting to observe that all these oncogenes identified in thyroid cancer activate a signaling pathway that results in an increased MAPK activity, according to which one specific signaling pathway that leads to MAPK activation plays a major role in the generation of PTC. However, other genetic lesions have also been reported in PTCs: decreased levels of PTEN and PTPRJ, a dual-specific phosphatase and a receptor type tyrosine phosphatase respectively , and alterations of the p27 kip protein function (Baldassarre et al 1999) represent frequent features of thyroid malignancies. p27 kip1 has classically been regarded as a cell-cycle inhibitor based on its potent inhibitory activity of cyclin E/cdk2 and the observation that its forced expression results in G1 arrest (Toyoshima & Hunter 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Also in thyroid malignant neoplasias, the impairment of the p27 function is very frequent: a reduction in p27 kip1 protein levels has been previously described in 10 out of 28 papillary carcinomas, 3 out of 9 follicular carcinomas, and 6 out of 8 anaplastic carcinomas. Moreover, 80% of p27 kip1 -expressing tumors shows an uncommon cytoplasmic localization of p27 kip1 protein, associated with a high cdk2 activity (Baldassarre et al 1999). Several components account for the reduced p27 protein levels in thyroid malignant neoplasias: both PTEN and PTPRJ, whose expression is drastically reduced in thyroid malignant neoplasias , increase the stability of the p27 protein.…”
Section: Introductionmentioning
confidence: 99%